PREVALENCE OF PSYCHOACTIVE SUBSTANCE USE AMONG SECURITY GUARDS AT TERTIARY CARE HOSPITAL: A CROSS-SECTIONAL STUDY - Mustafa, Ali Burhan; Babar, Muhammad Zafar Majeeed; Saleem, Muhammad; Zafar, Urooj; Farooq, Hamza; Munir, Nousheen; Khan, Tuba; Adil, Muhammad Amin (Journal of Pakistan Psychiatric Society, 2024)
Introduction: Drug addiction is a prevalent problem in Pakistan, and screening tools are available for diagnosis. Seeking guidance from healthcare professionals is important for appropriate treatment. Assessing addiction among security personnel is important for safety and policy formulation Aims & Objectives: This cross-sectional study aims to investigate drug addiction screening and its correlates among security guards in a tertiary care hospital. Materials & Methods: This cross-sectional study was conducted at Sheikh Zayed Medical College/Hospital in Rahim Yar Khan, Pakistan. Purposive convenience sampling was used to select a sample size of 184 Results: The study conducted among 184 security guards showed significant associations between gender, marital status, and age categories. A considerable proportion of guards were found to be overweight, had increased blood pressure, and substance use in the form of nicotine-related substances was found to be The study highlights the need for interventions promoting healthy lifestyles and substance use education and prevention efforts among security guards in such settings. Conclusion: This study revealed a prevalence of substance use among security guards in a tertiary care hospital in Pakistan and identified the need for interventions to promote healthy lifestyles and substance use education/prevention. Seeking guidance from healthcare professionals and implementing public health initiatives to address drug addiction and promote healthy lifestyles among security personnel are crucial.